KEBIJAKAN PEMERINTAH TERHADAP BANTUAN OPERASIONAL SEKOLAH (BOS) TENTANG PEMBIAYAAN PENDIDIKAN WAJIB BELAJAR 9 TAHUN DI SDN 08 PADANG BESI KOTA PADANG - Puryanto Puryanto; Dreizy Gustianda Y (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The government program makes a policy on School Operational Assistance (BOS) which is basically to provide funding for non-operational costs for basic education as an organizer of 9-year compulsory education. SDN 08 Padang Besi, Padang City, one of which received School Operational Assistance (BOS) funds. This research uses descriptive qualitative method, with purposive sampling technique. Collecting data by library method, interview, observation and literature review. This study uses the theory of George C. Edward III because the indicators are in accordance with the research. The formulation of the research problem is how the government's policy in School Operational Assistance (BOS) regarding the financing of 9-year compulsory education at SDN 08 Padang Besi, Padang City, is the obstacle in government policy on School Operational Assistance (BOS) regarding the financing of 9-year compulsory education at SDN 08 Padang Besi, Padang City, how are the efforts made to overcome the obstacles in the government's policy on School Operational Assistance (BOS) regarding the financing of 9-year compulsory education at SDN 08 Padang Besi, Padang City. The results showed that the policy had not been effective, it happened because not all policies were implemented by SDN 08 Padang Besi, Padang City. The lack of resources, both inadequate human resources from experts, both from facilities and infrastructure resources to support the implementation of services, and from elements service communication that has not been maximized and the attitude of the implementer who has not been committed to carrying out their duties. And finally, the need for SDN 08 Padang Besi, Padang City to fix the online service system during the corona virus 19 pandemic. The conclusion is that the policy carried out by SDN 08 Padang Besi Padang City is basically to help underprivileged students in financing 9-year compulsory education so that students those who are less able can receive learning well in the teaching and learning process at SDN 08 Padang Besi, Padang City.